Invasive Species Management : a Handbook of Principles and Techniques. - Clout, Mick N. (Techniques in Ecology & Conservation., 2009)
The management of Invasive Alien Species is a rapidly advancing field of applied ecology. This is an authoritative synthesis of the principles and techniques of preventing, eradicating and controlling these species, documenting lessons that have been learned and recommending 'best practice'.